Improving the wear life of a cocoa spray-drying unit - (:unkn) unknown (Leaf Coppin Publishing Co., 2002)
In the chocolate production process, the moisture content of ground cocoa is removed in a spray-drying unit, in which wet cocoa is pumped through a high-pressure pump. Wear occurs in this high-pressure pump, which can cause problems in the system. Originally, valves and beds were made of AISI 316 Ti austenitic stainless steel, and their average wear life was less than 280 h, obviously too short for use in industrial production. The aim of the research reported in this paper was to investigate ways to increase the wear life of these parts. In this respect six different materials were tested. Valves and beds were produced from four different steels and two powder metals. The steel parts were hardened by heat treatment. All the parts were electroplated with CrN or TiN. Wear life tests were carried out, and it was shown that AISI M2 high-speed steel valves and beds gave the longest wear lives.
Keywords: Stainless steel; Wear; Wear life; Wet cocoa